2021
DOI: 10.3390/met11101651
|View full text |Cite
|
Sign up to set email alerts
|

Carbonitriding of Forging Dies

Abstract: Forging dies have to resist high mechanical and thermal loads. Therefore, they are usually nitrided. Former investigations showed that the abrasive wear at the critical parts of the dies is much higher than the nitriding hardness depth. Carbonitriding offers the possibility to increase the hardness depth in shorter treatment times because of the higher treatment temperature. The (carbo-)nitrided surface region obtains a better hardness at elevated temperatures and a better wear resistance than the untreated st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…It has obvious advantages in energy saving and environmental protection [30][31][32]. There are various methods of chemical heat treatment, typically named after the infiltrated elements or compounds formed, such as nitriding [33][34][35], carburizing [36][37][38], nitrocarburizing [39], sulfurizing [40], oxidizing [41], among others.…”
Section: Solid Lubrication Layer Plasma Surface Preparation Technolog...mentioning
confidence: 99%
“…It has obvious advantages in energy saving and environmental protection [30][31][32]. There are various methods of chemical heat treatment, typically named after the infiltrated elements or compounds formed, such as nitriding [33][34][35], carburizing [36][37][38], nitrocarburizing [39], sulfurizing [40], oxidizing [41], among others.…”
Section: Solid Lubrication Layer Plasma Surface Preparation Technolog...mentioning
confidence: 99%
“…8 Thi Chieu et al 13 found that the microhardness of carbonitriding SCM420 was enhanced from 40 HRC for the untreated material to 65 HRC. In addition, Hoja et 14 found that the carbonitriding treatment improved the wear resistance of forging dies. Selcuka et al 15 have demonstrated that carbonitriding for low carbon and low alloyed steel (1020 and 5115 steels) was a more accurate process compared to gas carburizing.…”
Section: Introductionmentioning
confidence: 99%